Comparative Analysis of the Financial Performance of Islamic Banks and Conventional Banks During the COVID-19 Pandemic in Indonesia - Nabilah, Azmi (CV. Ulil Albab Corp, 2025)
The COVID-19 pandemic has significantly affected the global financial sector, including the banking industry in Indonesia. This study aimsl to analyze thel differences inl financial performancel between Islamicl and conventionall commercial banksl during thel pandemic period from 2020 to 2023. The research adopts a purposive sampling method, selecting banks that consistently disclosed complete financial data throughout the observation period. The study employs the REC (Risk Profile, Earnings, and Capital) framework to evaluate financial performance, focusing on key indicators such as Non-Performing Financing/Loans (NPF/NPL), Return on Assets (ROA), Operational Efficiency Ratio (BOPO), Capital Adequacy Ratio (CAR), and liquidity ratios including Financing to Deposit Ratio (FDR) and Loan to Deposit Ratio (LDR). The Mann-Whitney U test is utilized as a non-parametric approach to determine the presence of statistically significant differences between the two banking groups. The results reveal that Islamic and conventional banks exhibit significantl differences inl NPF/NPL, ROA, BOPO, andl CAR during thel pandemic, while no significant disparity is observed in FDR and LDR, indicating comparable liquidity performance between the two banking models. These findings are expected to provide useful insights for stakeholders in assessing the stability and responsiveness of banking institutions during financial crises.”